Genetic characterisations of four goat breeds in Malaysia assessed using microsatellites - Abu Bakar, Amie Marini (2014)
The genetic characterisation of goat breeds in Malaysia as a genetic resource is essential for genetic improvement as well as a conservation strategy. The goat breeds in Malaysia comprise small-framed animals made up of the original Katjang goat with the addition of larger framed exotic goats such as Jamnapari and Boer. The local indigenous Katjang goat has a reasonably high degree of tolerance to the local environment. On the other hand, the Boer, Jamnapari and Savanna which are introduced breeds are well adapted in Malaysia. However, little information is available on the goat breeds’ genetic characteristics or genetic variabilities. Basically, information about the genetic background of a breed and its populations is required for proper breeding. Data based on adequate genetic studies for goat characterisation and their similarities are still lacking. The goat populations have to be genetically characterised because genetic information is considered as the primary and essential starting point of any goat husbandry project. Knowledge of the genetic variability of a species is a core element for the conservation and exploitation of animal diversity for breeding purposes. Thus, this study was conducted to evaluate the genetic variabilities of the goat breeds in Malaysia, namely Katjang the indigenous goat and the exotic Jamnapari, Boer and Savanna breeds, by using microsatellite markers for proper breeding, selection and conservation purposes. Blood samples were randomly sampled from Katjang, n=37, Jamnapari, n=34, Boer,n=40 and Savanna, n=40. Thirty microsatellite primer pairs suggested by FAO/ISAG and seven microsatellite loci from other studies were used for the genetic diversity studies in the goats. The microsatellite markers were optimised using pooled DNA at different polymerase chain reaction (PCR) conditions followed by screening individuals for polymorphisms. The polymorphic microsatellite loci were used for the genetic diversity studies. Thirty out of the 37 microsatellite loci were polymorphic in all four goat breeds,while six loci were monomorphic and one locus failed to amplify for the Boer goat breed suggesting that it was monomorphic for the null allele. The mean number of observed alleles ranged from 5.43 to 5.90. Meanwhile the observed heterozygosity values (Ho) were lower than the expected heterozygosities for the goat breeds studied. The Jamnapari and Boer goat breeds had the highest Ho (0.43), followed by the Savanna (0.42) and the Katjang showed the lowest Ho (0.36). Genotypic linkage disequilibrium was observed between several loci but there was no consistency across the breeds. The overall mean inbreeding coefficient (FIS) of 0.43 indicated the occurrence of inbreeding in all the four breeds studied. The mean FIT and FST values of 0.46 and 0.06, respectively measured the degree of differentiation within and among breeds. The FST value indicated a lack of genetic differentiation among the goat breeds. The Nei’s genetic identities among the four goat breeds ranged from 80% - 87%. The highest genetic distance value was observed between the Katjang and the Savanna goat breeds (0.2171) while the Boer and the Savanna goat breeds were found to be the most similar with a genetic distance value of 0.1325. Based on this study it can be concluded that there are some genetic variations in the four goat breeds in Malaysia, although the Katjang has a slightly lower genetic diversity. However, further screening of the goat breeds, utilising more breeds and larger sample sizes are needed to ascertain more accurately the variability of the goat breeds in Malaysia. Microsatellite marker typing using the capillary technique and other more sensitive marker systems like SNP should also be considered. In addition, consideration should be given to genome mapping, using the latest high throughput genotyping platforms to obtain the best genomics solutions and applications.